Fabricación y caracterización eléctrica de microelectrodos de silicio para registro de señales nerviosas - Aragón Puerto, Jorge Enrique; Calleja Arriaga, Wilfrido (Revista Mexicana de Ingenieria Biomedica, 2003)
The use of microelectrodes for the extracelular recording of the bioelectrical signals generated in the interior of the excitable tissue (neurons), is one of the most important techniques for the study of the peripheral and central nervous system at cellular level. It has been demonstrated that the use of the techniques of manufacture of integrated circuits permits to obtain planar microelectrodes (PME’s) with a high degree of control in the recording area dimensions, geometry and interelectrodes spacings, as well as a sharpened insertion profile and uniform and roughen free walls. In this report, are presented the various stages of basic electrical characterization of the manufactured devices, including the methodology, used equipment, experimental assembly and proposal of the microelectrodes packaging.